2022
DOI: 10.3390/agronomy12081952
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Accumulation in Cereal Crops and Tobacco: A Review

Abstract: Cadmium (Cd) is a toxic heavy metal with no known biological function in plants and one of the most toxic substances released into the environment. Crops, such as rice, maize, wheat and tobacco are the major sources of Cd for humans. Cd toxicity inhibits crop growth and development by affecting many central physiological and biochemical processes, and finally it affects human health via the food chain. To adapt to Cd toxicity, crops have evolved a series of detoxification mechanisms. Immediate responses includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 131 publications
0
6
0
Order By: Relevance
“…The differences found are due to multiple factors such as the origin of the samples, the intrinsic characteristics of the plants (uptake, accumulation and metabolism), the presence of these elements in the crop soil and in the irrigation water [ 2 , 3 , 23 , 40 42 ]. Whereas, in the case of cereal derivatives, the differences found, in addition to the factors mentioned above, may be due to the addition of other ingredients (additives, salt, anti-caking agents, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences found are due to multiple factors such as the origin of the samples, the intrinsic characteristics of the plants (uptake, accumulation and metabolism), the presence of these elements in the crop soil and in the irrigation water [ 2 , 3 , 23 , 40 42 ]. Whereas, in the case of cereal derivatives, the differences found, in addition to the factors mentioned above, may be due to the addition of other ingredients (additives, salt, anti-caking agents, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…The differences between cereals in the two regions may be due to multiple factors. For example, in the case of Cd, whose highest concentration was found in Madeira, this may be due to the fact that the samples from this region included cereals such as rice or oats, which tend to accumulate higher concentrations of this metal [ 42 ]. In the case of Pb, it is found that the content in the products collected in the Azores stands out, this may be due to the fact that the samples from this region are wheat and maize flour, which tend to accumulate higher concentrations of this metal [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tobacco products use leaves, so Cd control is the most important work in tobacco leaf production. Mei et al also emphasized that Cd is a highly toxic heavy metal without any known biological function in plants, making it one of the most hazardous substances released into the environment [ 49 ]. Crops, including rice, maize, wheat, and tobacco, serve as significant sources of Cd exposure for humans.…”
Section: Discussionmentioning
confidence: 99%
“…OsHMA3 and ZmHMA3 have been found to affect root-to-shoot Cd translocation in rice and maize by mediating its efflux into vacuoles (Miyadate et al, 2011). Besides, ZIP, IRT, and ABC families were also found to be involved in the efflux and uptake of Cd (Mei et al, 2022;Tang et al, 2021). In addition, several transcription factors (TFs), such as MYBs and WRKYs, have also been found to be activated in plants under Cd stress (Opdenakker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%